Exploring the business model canvas of mazars group: A comprehensive analysis - Possner, Putri Alexandra; Tanaya, Olivia (Institute of Computer Science (IOCS), 2023)
This journal article explores the complex business model of Mazars Group, a global professional service provider specializing in audit, tax, and advisory services. Through the lens of the Business Model Canvas (BMC), critical elements shaping Mazars' operations, including key partnerships, activities, resources, value propositions, customer relationships, channels, customer segments, cost structure, and revenue streams, are thoroughly analyzed. The study employs a qualitative approach, combining insights from interviews with a senior associate and web searches to understand Mazars' business model comprehensively. Mazars' commitment to service quality is emphasized, acknowledging the evolving landscape of technology and competition. The company's competitive advantage derives from critical factors such as strategic partnerships with law firms, consulting firms, and technology providers, extensive global reach, diverse services, and a personalized client approach. The marketing strategy is evaluated, with a recommendation to incorporate Google Ads to enhance visibility and capitalize on online consumer trends. The article highlights Mazars' success in delivering high-quality, integrated services to diverse client segments, ranging from startups to large enterprises and non-profit organizations. The firm's cost structure, revenue diversification, and global presence contribute to its resilience in the professional services industry. Mazars Group's enduring success serves as a valuable case study for professionals, academics, and businesses navigating the complexities of the global economy